ON HYBRIDISATION IN CONTEMPORARY SLOVAK PROSE - SOUCKOVA, MARTA (Bohemica Olomucensia, 2023)
In my paper, I see hybridisation as the mixing of multiple, often disparate elements. This term is used in literary studies mainly in connection with postmodernism and its other features (intertextuality, fragmentation, eclecticism, etc.). In Slovak post-revolutionary prose, the boundaries between arts, media, types or genres are often crossed, and there is an increasing number of works that oscillate between non-fiction and fiction, biography and fiction, journalism (reportage) and fiction, popular and artistic literature, or between the arts (visual, film and literary arts). In my paper, I will discuss prose published in 2019-2020: Katarina Kucbelova's book Cepiec, Ivana Gibova's comic short story collection Eklektik Bastard, Veronika Sikulova's non-novel Tremolo ostinato, and Natasa Holinova's prose Pripad starej damy, which each in a different way break the boundaries of genres or artistic literature. In particular, I will be interested in whether the hybridisation in the analysed prose works, i.e. whether an aesthetically effective form emerges through the crossing of practices from different fields.
Keywords: Slovak prose since 2000; hybridisation; functionality